Selective organic carbon losses from soils by sheet erosion and main controls. Issue 10 (16th March 2016) - Müller‐Nedebock, Daniel; Chivenge, Pauline; Chaplot, Vincent
Abstract: Although the impact of sheet erosion on the selective transportation of mineral soil particles has been widely investigated, little is yet known about the specific mechanisms of organic carbon (OC) erosion, which constitutes an important link in the global carbon cycle. The present study was conducted to quantify the impact of sheet erosion on OC losses from soils. Erosion plots with the lengths of 1‐ and 5‐m were installed at different topographic positions along a hillslope in a mountainous South African region. A total of 32 rainfall events from a three years period (November 2010 up to February 2013), were studied and evaluated for runoff ( R ), particulate and dissolved organic carbon (POCL and DOCL ). In comparison to the 0–0·05 m bulk soil, the sediments from the 1‐m plots were enriched in OC by a factor 2·6 and those from the 5‐m long plots by a factor of 2·2, respectively. These findings suggest a preferential erosion of OC. In addition, total organic carbon losses (TOCL ) were incurred mainly in particulate form (~94%) and the increase in TOCL from 14·09 ± 0·68 g C m −1  yr −1 on 1‐m plots to 50·03 ± 2·89 g C m −1  yr −1 on 5‐m plots illustrated an increase in sheet erosion efficiency with increasing slope length. Both TOCL and sediment enrichment in OC correspondingly increased with a decrease in soil basal grass cover. The characteristics of rainstorms had no significant impact on the selectivity of OC erosion. The results accrued in this study investigating the links between sheet erosion and OC losses, are expected to be of future value in the generation of carbon specific erosion models, which can further help to inform and improve climate change mitigation measures. Copyright © 2016 John Wiley & Sons, Ltd.